Solve for u.
4u²+3=-8u
If there is more than one solution, separate them with commas.
If there is no solution, click on "No solution."

Respuesta :

Answer:

u = [tex]-\frac{1}{2}[/tex]   ;  u = [tex]-\frac{3}{2}[/tex]

Step-by-step explanation:

4u² + 3 = -8u

4u² + 3 + 8u = -8u + 8u       (add 8u both sides)

4u² + 8u + 3 = 0                    simplify

using quadratic equation:

      - 8 ± √ (8² - 4 * 4 *3)

u = ------------------------------

               2 * 4

u = [tex]-\frac{1}{2}[/tex]   ;  u = [tex]-\frac{3}{2}[/tex]

ACCESS MORE